2021
DOI: 10.3389/fmed.2021.702436
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Speed and High-Speed Resistance Training Programs on Frailty Status, Physical Performance, Cognitive Function, and Blood Pressure in Prefrail and Frail Older Adults

Abstract: Aim: The current study investigated the effects of low-speed resistance training (LSRT) and high-speed resistance training (HSRT) on frailty status, physical performance, cognitive function and blood pressure in pre-frail and frail older people.Material and Methods: Sixty older adults, 32 prefrail and 28 frail, were randomly allocated into LSRT, HSRT, and control group (CG). Before and after intervention periods frailty status, blood pressure, heart rate, and a set of physical performance capabilities and cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 139 publications
(207 reference statements)
0
28
2
Order By: Relevance
“…Furthermore, in a meta-analysis evaluating the effect of training at high versus moderate intentional speeds, no significant improvements were found for either exercise modality [ 179 ]. In a recent study by Coelho-Júnior and Uchida [ 180 ], the effect of a 16-week training program on functional parameters in prefrail and frail individuals was evaluated. Participants were randomized into a control group, a low-speed strength training group and a high-speed strength training group.…”
Section: Impact Of Physical Activity/exercise On Aged Skeletal Muscle...mentioning
confidence: 99%
“…Furthermore, in a meta-analysis evaluating the effect of training at high versus moderate intentional speeds, no significant improvements were found for either exercise modality [ 179 ]. In a recent study by Coelho-Júnior and Uchida [ 180 ], the effect of a 16-week training program on functional parameters in prefrail and frail individuals was evaluated. Participants were randomized into a control group, a low-speed strength training group and a high-speed strength training group.…”
Section: Impact Of Physical Activity/exercise On Aged Skeletal Muscle...mentioning
confidence: 99%
“…Across all studies, sample sizes ranged from 18 to 50. Seven studies (70%) [ 27 , 71 76 ] mixed both male and female participants. Most studies recruited from links with community-dwelling adults and organisations [ 27 , 71 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only one study provided a power calculation, Tiggemann, Dias [ 78 ]. Four studies (40%) [ 27 , 73 , 75 , 76 ] recorded their method of randomisation, all using a computerised random number generator. Only two studies (20%) included information regarding safety of RT or injuries/illnesses sustained during the intervention; Gray, Powers [ 27 ] reported no injuries and suggested MIRT as safe and effective, and Miszko, Cress [ 72 ] reported a 22% (11/50 participants) drop-out through injuries and/or personal medical reasons.…”
Section: Resultsmentioning
confidence: 99%
“…This finding supports experts’ opinion that physical activity should be the first-line therapy to counteract age-related sarcopenia [ 51 , 52 , 53 , 54 ]. Numerous studies have reported that different exercise training modalities might improve upper- and lower-limb muscle strength in older adults [ 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. Specific attention has been paid to resistance training-type exercise [ 62 ], since exercise aspects may be safely and easily adjusted to stimulate type II muscle fibers and produce significant improvements in muscle strength [ 62 ].…”
Section: Discussionmentioning
confidence: 99%